The New Testament interpreted : essays in honour of Bernard C. Lategan - Breytenbach, Cilliers, 1954-; Lategan, Bernard C.; Thom, Johan Carl, 1954-; Punt, J. (Novum Testamentum, Supplements, 2006)
This volume contains a collection of essays in honour of Bernard C. Lategan, a renowned specialist on the modern reception of the New Testament. Besides offering anayses of Lategan's own contribution to New Testament scholarship, the essays present and discuss interpretations of the New Testament from antiquity through contemporary critical scholarship. Topics covered include hermeneutical issues of historical Jesus research, intertextuality in antiquity, the interpretation of the New Testament in Africa, and the New Testament as literature. The collection thus provides a representative perspective on the diversity of New Testament scholarship in South Africa and elsewhere.